2015
DOI: 10.1016/j.eururo.2014.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Remission is a Prognostic Factor for Survival in Patients with Metastatic Renal Cell Carcinoma

Abstract: Background Response remains an important endpoint in clinical cancer trials. However, the prognostic utility of best tumor response in metastatic renal cell carcinoma (mRCC) remains vague. Objective To define the prognostic relevance of the depth of remission in mRCC Design, setting, and participants Pooled data of 2,749 patients from phase II and III clinical trials of the Pfizer data-base in mRCC was analyzed. Tumor-shrinkage was categorized by fractions of best percent change in the sum of the largest d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 20 publications
4
31
0
4
Order By: Relevance
“…For example, the depth of remission during first-line therapy proved to be an independent prognostic factor. Early tumor shrinkage and the depth of remission were significantly associated with an improved OS (16). However, early progression itself is technically not a baseline parameter, which will generate problems because clinicians cannot base therapeutic decision making on this parameter up front of first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the depth of remission during first-line therapy proved to be an independent prognostic factor. Early tumor shrinkage and the depth of remission were significantly associated with an improved OS (16). However, early progression itself is technically not a baseline parameter, which will generate problems because clinicians cannot base therapeutic decision making on this parameter up front of first-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it may be necessary to identify parameters that help individualize patient prognostication to provide an optimal sequential therapy for mRCC as a post-first-line setting. The significant impact of the tumor response to a targeted agent on the subsequent prognosis in patients with mRCC has been reported [12][13][14][15][16][17][18][19][20]. However, albeit significant antitumor activities from a clinical viewpoint, molecular-targeted agents have been shown to be characterized by a comparatively low level of tumor shrinkage due to the mechanisms mediating their activities against mRCC through the inhibition of angiogenesis rather than that of tumor cell proliferation [1].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, this study showed for the first time that the degree of ETS under second-line targeted therapy was proportional to OS among the four subgroups; that is, the median OS stratified according to the degree of ETS, as described above, was 45.8, 30.9, 22.1 and 14.2 months, respectively. To date, there have been several studies demonstrating the significant impact of the level of tumor shrinkage on survival in patients with mRCC receiving first-or second-line targeted therapy [12][13][14][15][16][17][18][19][20]. For example, Seidel et al reported the close correlation between OS and tumor shrinkage early in the course of first-line targeted therapy, which was stratified into the following five groups: tumor remission of -100 to -60 %, -59 to -30 %, -29 to 0 %, or gain of 1 to 19 %, C20 % [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superior outcome was detected in patients with any tumor shrinkage on targeted therapies, with an exceptional response in those with a tumor shrinkage of at least 60% [4]. This paves the way for novel concepts in mRCC trials, indicating that the enlargement of the fraction of patients with deep remission will improve survival.…”
Section: Introductionmentioning
confidence: 99%